ENOS transfection of adipose‐derived stem cells yields bioactive nitric oxide production and improved results in vascular tissue engineering. (14th January 2013) - McIlhenny, Stephen; Zhang, Ping; Tulenko, Thomas; Comeau, Jason; Fernandez, Sarah; Policha, Aleksandra; Ferroni, Matthew; Faul, Elizabeth; Bagameri, Gabor; Shapiro, Irving; DiMuzio, Paul
Abstract: This study evaluates the durability of a novel tissue engineered blood vessel (TEBV) created by seeding a natural vascular tissue scaffold (decellularized human saphenous vein allograft) with autologous adipose‐derived stem cells (ASC) differentiated into endothelial‐like cells. Previous work with this model revealed the graft to be thrombogenic, likely due to inadequate endothelial differentiation as evidenced by minimal production of nitric oxide (NO). To evaluate the importance of NO expression by the seeded cells, we created TEBV using autologous ASC transfected with the endothelial nitric oxide synthase (eNOS) gene to produce NO. We found that transfected ASC produced NO at levels similar to endothelial cell (EC) controls in vitro which was capable of causing vasorelaxation of aortic specimens ex vivo . TEBV ( n  = 5) created with NO‐producing ASC and implanted as interposition grafts within the aorta of rabbits remained patent for two months and demonstrated a non‐thrombogenic surface compared to unseeded controls ( n  = 5). Despite the xenograft nature of the scaffold, the TEBV structure remained well preserved in seeded grafts. In sum, this study demonstrates that upregulation of NO expression within adult stem cells differentiated towards an endothelial‐like lineage imparts a non‐thrombogenic phenotype and highlights the importance of NO production by cells to be used as endothelial cell substitutes in vascular tissue engineering applications. Copyright © 2013 John Wiley & Sons, Ltd.